G423(P) From reflection to action: a multimodal, interactive approach to enhancing training on child refugee health. (12th March 2018) - Singh, G; Sen, C
Abstract : Aims: Child refugees have specific but complex health needs that place significant demands on health systems and those working within them. Public and professional expectation is that health workers are proficient in caring for this vulnerable population. 1–3 Despite increasing numbers of child refugees to the UK, 4 health professionals report feeling ill-equipped to address these needs, and unable to fulfil their ethical obligations. 5 We designed a training course to address this gap, and evaluated the impact on professional confidence and competency in caring for child refugees. Methods: Our interdisciplinary, one-day course for child health professionals aimed to deepen understanding of: the geopolitical origins of the 'migration crisis'; the physical and mental health needs of child refugees; and advocacy for vulnerable populations. Following established pedagogical theory, 6 we utilised a multimodal and interactive model: digital technology; skills workshops; first-hand testimonies and the use of literary and visual art were employed alongside more traditional lectures. An online pre- and post-course questionnaire with multiple-choice and free-text questions captured professionals' perceptions about confidence and competence. Results: Of the 190 course delegates, responses were as follows (table 1): For delegates, the biggest obstacles to managing the 'migrant crisis' were: lack of awareness of problems faced by refugees (47% – 50/107) and lack of collaboration between health and social care (31% – 33/107). Free-text responses consistently reflected a desire to learn how to: advocate for child refugees in both local and national spheres; educate other professionals and the public about refugee needs; and be more active politically and as a volunteer. Conclusion: This study confirms significant demand for professional training around child refugee health needs. Our interdisciplinary, multimodal and interactive approach increased confidence of delegates to manage child refugee physical and mental health, stimulated interagency collaboration and provided a platform for actualising professional ethical and advocacy responsibilities to vulnerable populations. This model has potential for professional training elsewhere.